Reactivity of Amino and Methyl Groups in 3-amino-2-methyl-3,4-dihydro-4-oxo-quinzoline towards Condensation with Aldehydes - Lal, K.B. (Asian Journal of Chemistry, 2010)
3-Amino-2-methyl-3,4-dihydro-4-oxoquinazoline was prepared(Scheme I-III) and was found to condense with benzaldehyde intwo stages. The first molecule of benzaldehyde reacted with theamino group at N(3) and the second molecule reacted with themethyl group at C(2). This preferential reactivity of the two groupswas studied.